2006
DOI: 10.1111/j.1399-3046.2006.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful unrelated mismatched cord blood transplantation in an infant with severe combined immunodeficiency and Mycobacterium bovis bacillus Calmette‐Guèrin disease

Abstract: The case reported here of an infant who presented with Pneumocystis carinii pneumonia, CD4+ lymphopenia, and hypogammaglobulinemia attributable to severe combined immunodeficiency (SCID). This report discussed treatment of Mycobacterium bovis bacillus Calmette-Guèrin disease with unrelated cord blood transplantation in addition to antituberculous therapy, by adoptively transferring donor immunity with induction of mixed chimerism. Because of the unique nature of umbilical cord blood hematopoietic cells, engraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
9
1
Order By: Relevance
“…Three of them had no prior evidence of infection, yet developed either local or disseminated infection following HSCT as in our case . Sixteen of them had infection prior to HSCT, and dissemination process had occurred before transplantation as a result of inadequate immunity …”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Three of them had no prior evidence of infection, yet developed either local or disseminated infection following HSCT as in our case . Sixteen of them had infection prior to HSCT, and dissemination process had occurred before transplantation as a result of inadequate immunity …”
Section: Discussionmentioning
confidence: 50%
“…Abu Arja et al reviewed 19 reported cases of BCG infection that had been reported in post‐transplant patients with PID . Three of them had no prior evidence of infection, yet developed either local or disseminated infection following HSCT as in our case .…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations